Kuwabara Payne McKenna Blumberg Architects. (De Gruyter : Birkhäuser, 2013)
Kuwabara Payne McKenna Blumberg Architects is one of most innovative architectural offices in North America today. They have made a name for themselves both for their integrated design process embodying collaboration with experts, clients and future users as well as the diversity of their aesthetically refined and finely detailed designs.